2020
DOI: 10.1111/cup.13902
|View full text |Cite
|
Sign up to set email alerts
|

Insulinoma‐associated 1: A sensitive marker of neuroendocrine differentiation in cutaneous and metastatic neuroendocrine tumors

David S. Cassarino

Abstract: Insulinoma-associated 1 (INSM1) is a nuclear zinc finger transcription factor, which is a sensitive and specific marker of neuroendocrine differentiation. INSM1 binds to DNA and is involved in the expression of multiple neuroendocrine-related genes, including those encoding for chromogranin and synaptophysin; it also regulates other proteins such as cyclin D1 involved in the cell cycle. 1-3 INSM1 was first discovered in human glucagonoma and insulinoma tumor tissues, and has been shown to be expressed in norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…In a prior study, 2 we identified insulinoma-associated protein 1 (INSM1) and MUC2 as sensitive markers for the identification of EMPSGC and confirmed the ability of INSM1 to increase recognition of neuroendocrine differentiation in these low-grade mucinous tumors when compared with the conventional markers synaptophysin and chromogranin. While reviewing the literature, we noted that the vast majority of primary cutaneous mucinous and nonmucinous adnexal carcinoma reported have not been subjected to this sensitive neuroendocrine marker INSM1, 3 and most cases of reportedly non-neuroendocrine mucinous primary cutaneous sweat gland carcinoma are solitary and/or from historical series, thus the true prevalence of neuroendocrine differentiation in these higher grade tumors is unknown, potentially weakening the conclusions of Agni et al 1 …”
mentioning
confidence: 91%
See 1 more Smart Citation
“…In a prior study, 2 we identified insulinoma-associated protein 1 (INSM1) and MUC2 as sensitive markers for the identification of EMPSGC and confirmed the ability of INSM1 to increase recognition of neuroendocrine differentiation in these low-grade mucinous tumors when compared with the conventional markers synaptophysin and chromogranin. While reviewing the literature, we noted that the vast majority of primary cutaneous mucinous and nonmucinous adnexal carcinoma reported have not been subjected to this sensitive neuroendocrine marker INSM1, 3 and most cases of reportedly non-neuroendocrine mucinous primary cutaneous sweat gland carcinoma are solitary and/or from historical series, thus the true prevalence of neuroendocrine differentiation in these higher grade tumors is unknown, potentially weakening the conclusions of Agni et al 1 …”
mentioning
confidence: 91%
“…In a prior study, 2 we identified insulinoma-associated protein 1 (INSM1) and MUC2 as sensitive markers for the identification of EMPSGC and confirmed the ability of INSM1 to increase recognition of neuroendocrine differentiation in these low-grade mucinous tumors when compared with the conventional markers synaptophysin and chromogranin. While reviewing the literature, we noted that the vast majority of primary cutaneous mucinous and nonmucinous adnexal carcinoma reported have not been subjected to this sensitive neuroendocrine marker INSM1, 3 and most cases of reportedly non-neuroendocrine mucinous primary cutaneous sweat gland carcinoma are solitary and/ or from historical series, thus the true prevalence of neuroendocrine differentiation in these higher grade tumors is unknown, potentially weakening the conclusions of Agni et al 1 For this study, we therefore proposed to evaluate INSM1 labeling in a cohort of mucinous and nonmucinous primary cutaneous adenocarcinoma from our single cancer center and to correlate the characterized neuroendocrine phenotypes with patients' disease-related outcomes, pathologic features, and other clinical data. A secondary aim was to further validate the utility of INSM1 in distinguishing periocular neoplasms, including sebaceous carcinoma, basal cell carcinoma (BCC), and benign apocrine neoplasms.…”
mentioning
confidence: 99%
“…Immunohistochemical staining for MCC commonly involves several markers, including cytokeratin 20 (CK20), neuron-specific enolase (NSE), and insulinoma-associated protein 1 (INSM1) [12]. INSM1 has emerged as a valuable marker for neuroendocrine differentiation and is increasingly used in the diagnosis of MCC due to its high specificity and sensitivity for MCC [12,13].…”
Section: Introductionmentioning
confidence: 99%